Evaluasi Efektivitas Fotokatalisis TiO₂ dan H₂O₂ terhadap Pengolahan Limbah Cair dari Industri Tahu - Meta Kholjana, Ahjul; Masriatini, Rully; Husnah (Program Studi Teknik Kimia, Universitas Pamulang, 2026)
The tofu industry in Indonesia significantly contributes to the national economy but also poses environmental challenges due to the liquid waste it generates. This wastewater contains organic and inorganic pollutants such as BOD, COD, TSS, and pH levels that do not meet effluent quality standards, potentially harming aquatic ecosystems. This study aims to evaluate the effectiveness of a photocatalytic process using titanium dioxide (TiO₂) and hydrogen peroxide (H₂O₂), activated by artificial UV-C light and sunlight, in reducing pollutants in tofu industrial wastewater. The treatment was conducted with a fixed concentration of 50 mg/L TiO₂ and 140 mL H₂O₂ per 1000 mL of wastewater, with contact times ranging from 30 to 60 minutes. Results showed that the TiO₂-H₂O₂ combination reduced COD by up to 84.78%, BOD by 76.75%, and TSS by 78.37%, while increasing the pH toward acceptable limits. The optimal degradation occurred under sunlight exposure for 60 minutes. This method offers a promising, eco-friendly, and cost-effective wastewater treatment solution.